Design of a High-Efficiency GaN High-Electron Mobility Transistor Microwave Power Amplifier - Luong, Duy Manh; Nguyen, Huy Hoang (Old Journal, 2020)
This study presents a design procedure to obtain high-efficiency for microwave power amplifier. The designed amplifier uses a GaN high electron mobility transistor as an active device. Matching networks including input and output networks are realized using Megtron6 substrate microstrip lines. The designed amplifier operates at 2.1 GHz band. The simulated results show that the amplifier delivers a maximum power-added efficiency of 73.2% at output power and power gain of 47.8 dBm and 13.8 dB, respectively. This promising designed performance makes this amplifier to be an excellent candidate for use in modern wireless communication systems like radar, mobile network, and satellite communications.